Response of Sugarbeet (Beta vulvaris) to Irrigation Scheduling under Drip and Surface Irrigation - Sherring, Arpan; Lordwin Grirish Kumar, J.; Mishra, S.N. (Journal of Soil and Water Conservation, 2022)
Field experiment was conducted at Irrigation Research Farm of Allahabad Agricultural Institute-Deemed University, Allahaoad, U.P., India, during the winter crop growing season of 2002-2003 on clay loam soil to study the effect of four irrigation levels of pan evaporation replenishment (50%, 100%, 150% and 200%) on marketable root yield, irrigation production efficiency and economic return of sugarbeet. Irrigation at 150% of pan evaporation replenishment gave higher marketable root yield (30.22 t/ha) whereas irrigation at 50% of pan evaporation replenishment resulted in higher irrigation production efficiency (20.12 kg/m3). A further increase in irrigation level reduced marketable root yield and irrigation production efficiency (13.07 kg/m3) of sugarbeet followed by check basin irrigation method. Irrigation at 150% of pan evaporation replenishment gave the higher gross return, net return and benefit cost ratio but it decreased considerably svith the further increase in amount of irrigation. The seasonal water applied/ irrigation levels and marketable root yield, gross return, net return and benefit cost ratio exhibited a strong quadratic relationship which can be used for allocating irrigation water within and between the crops to optimize the economic return under drip and check basin irrigation methods.